Accelerated Chemical Reactions and Organic Synthesis in Leidenfrost Droplets. Issue 35 (28th July 2016) - Bain, Ryan M.; Pulliam, Christopher J.; Thery, Fabien; Cooks, R. Graham
Abstract: Leidenfrost levitated droplets can be used to accelerate chemical reactions in processes that appear similar to reaction acceleration in charged microdroplets produced by electrospray ionization. Reaction acceleration in Leidenfrost droplets is demonstrated for a base‐catalyzed Claisen–Schmidt condensation, hydrazone formation from precharged and neutral ketones, and for the Katritzky pyrylium into pyridinium conversion under various reaction conditions. Comparisons with bulk reactions gave intermediate acceleration factors (2–50). By keeping the volume of the Leidenfrost droplets constant, it was shown that interfacial effects contribute to acceleration; this was confirmed by decreased reaction rates in the presence of a surfactant. The ability to multiplex Leidenfrost microreactors, to extract product into an immiscible solvent during reaction, and to use Leidenfrost droplets as reaction vessels to synthesize milligram quantities of product is also demonstrated. Abstract : Chemical reactions can be accelerated in Leidenfrost levitated droplets in processes that are similar to reaction acceleration in charged microdroplets produced by electrospray ionization. Acceleration factors of 2 to 50 compared to the corresponding bulk‐phase reactions were achieved for a range of transformations.